The collaboration of Maria Amália Vaz de Carvalho with O Paiz (1884-1889): Survey of texts and preliminary research notes - De Luca, Tania Regina [UNESP] (2022)
The project The necessity for discussing the absent: Women chroniclers in the nineteenth century press: Research in collections (UCL, Unesp, Unicamp) aims to systematically locate the collaboration of writers Maria Amália Vaz de Carvalho (1847-1921), Maria Benedita Câmara Bormann (pseudonym Délia, 1853-1895), Emília Moncorvo Bandeira de Melo (pseudonym Carmen Dolores, 1852-1910) and Júlia Lopes de Almeida (1862-1934) in the Rio de Janeiro press during the Belle Époque. The survey is based on the digital collection of periodicals available at the Hemeroteca Digital Brasileira, Brazilian National Library. In addition to organizing free access digital editions, it intends to reassess the female presence in the late nineteenth-century press, in order to give more visibility to women's journalism and construct new narratives around female voices, which are still largely silent. The article focuses on Maria Amália's career until joining O Paiz, and presents her five-year collaboration with this daily newspaper which (although not continuously) amounts to almost one hundred articles. This paper aims to present the general features of this voluminous set of texts from a diverse range of genres - crônicas, short stories, essays and book reviews - and to highlight its multiple possibilities for analysis. It should be noted that this is a work in progress.